Differences in fibroid vascularity after three months of pre-treatment with leuprolide acetate or ulipristal acetate: A pilot study. (February 2020) - Frijlingh, Marissa; De Milliano, Inge; Hehenkamp, Wouter. J.K.; Huirne, Judith. A.F.
Abstract: Objectives: To investigate differences in volume and fibroid vascularity expressed in vascular index after three months of (pre-)treatment with leuprolide acetate (LPA) or ulipristal acetate (UPA). Study design: Prospective pilot study of 23 premenopausal women with uterine fibroids. Patients who started with LPA or UPA and had at least one fibroid with a size between 3 and 12 cm, were included consecutively. Per patient one fibroid was evaluated. The ultrasound was performed at baseline and after three months using LPA or UPA using a standardized protocol. 3D scans were evaluated using VOCAL software to calculate outcomes of volume, vascular index (VI) without shell ("shell off") and of the inner shell. Results: Four patients in the LPA group were additionally excluded from analyses due to insufficient quality of 3D scans. In the ten remaining patients (pre-)treated with LPA both volume and vascular indices of the fibroid reduced significantly after three months from a median of 224.3 cm 3 (IQR 338.0) to 124.8 cm 3 (IQR 186.1) ( p = 0, 05); median VI fibroid (shell off) reduced from 4.30 (IQR 4.72) to 0.93 (IQR 1.54) ( p = 0, 05); and VI inner capsule from 6.34 (IQR 7.51) to 1.28 (IQR 2.13) ( p = 0, 05). After UPA ( n = 9) changes in fibroid volume and vascular indices did not reach statistical significance. Volume reduced from 248.5 cm 3 (IQR 271.9) to 140.7 cm 3 (IQR 209.4) ( p > 0, 05); median VI fibroid (shell off) from 2.97 (IQR 3.81) to 2.90 (IQR 4.82) ( p > 0, 05); and VI inner capsule from 2.56 (IQR 7.48) to 2.89 (IQR 4.83) ( p > 0, 05). A strong positive correlation was found between the VI of the fibroid (shell off) at baseline with the volume change after three months of LPA use (LPA r = 0.636, p = 0.048, 95% CI = -0.03 – 1.00). Conclusion: In this pilot study we observed a consistent and statistically significant decrease in VI and fibroid volume after three months of LPA treatment in patients with uterine fibroids. The decrease in fibroid volume and VI was less consistent after UPA use. The strong correlation between the VI at baseline and volume reduction, may in theory be used to predict the volume reduction after LPA.